2021
DOI: 10.34197/ats-scholar.2020-0023oc
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Simulation-based Mastery Learning on Resident Skill Managing Mechanical Ventilators

Abstract: Background: Caring for patients requiring mechanical ventilation is complex, and residents may lack adequate skill for managing these patients. Simulation-based mastery learning (SBML) is an educational model that trains clinicians to a high standard and can reduce complications. The mastery learning model has not been applied to ventilator management. Objective: The purpose of this study was to determine whether SBML, as compared with traditional training, is an effective st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
18
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 43 publications
1
18
0
1
Order By: Relevance
“…We chose to apply the SBA at the beginning of rotation because one of our aims was to identify the most common knowledge gaps, to address them during the rotation. Our finding is similar to that of a recent study ( 30 ) in which investigators used simulation to assess baseline skills, as a teaching tool in the form of deliberate practice, and to assess end-of-rotation skills. They found that at the beginning of ICU rotation the median score was 52%, and it increased to 86% at the end of rotation.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…We chose to apply the SBA at the beginning of rotation because one of our aims was to identify the most common knowledge gaps, to address them during the rotation. Our finding is similar to that of a recent study ( 30 ) in which investigators used simulation to assess baseline skills, as a teaching tool in the form of deliberate practice, and to assess end-of-rotation skills. They found that at the beginning of ICU rotation the median score was 52%, and it increased to 86% at the end of rotation.…”
Section: Discussionsupporting
confidence: 88%
“…Although written assessments such as the MCE can be used to assess learning, SBAs require that learners apply knowledge when they operate a mechanical ventilator in a scenario that mimics real clinical scenarios, providing a more complete assessment of competence. Previous studies showed that simulation in MV can provide lasting knowledge and prepare residents to safely manage ventilated patients ( 30 , 39 , 40 ), and SBAs have been successfully used to identify learning gaps and provide remediation ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Simply relying on experiential learning could lead to patient harm if learners are called upon to provide MV management despite a paucity in background knowledge and training. Prior studies of MV education have shown simulation-based practical examinations to be superior to traditional assessments ( 10 , 13 , 14 ). In this study, the authors make an important contribution by developing an MV curriculum in an objective structured clinical examination format that incorporates core competencies required to care for critically ill patients receiving MV ( 15 ).…”
mentioning
confidence: 99%
“…Therefore, the participants’ learned knowledge and skill during their ICU rotation were not assessed by the SBA. Use of a pretest paired with deliberate practice and feedback before a posttest has been shown to successfully get learners to a mastery standard for MV management and other common ICU procedures ( 10 , 11 ). The learners in this study were not provided feedback on their SBA, nor were they allotted the opportunity for deliberate practice.…”
mentioning
confidence: 99%